The emerging role of intestinal stem cells in ulcerative colitis - Chen, Siqing; Qin, Zhang; Zhou, Sainan; Xu, Yin; Zhu, Ying (Frontiers in Medicine, 2025)
Ulcerative colitis (UC) is a chronic idiopathic inflammatory disease affecting the colon and rectum. Characterized by recurrent attacks, UC is often resistant to traditional anti-inflammatory therapies, imposing significant physiological, psychological, and economic burdens on patients. In light of these challenges, innovative targeted therapies have become a new expectation for patients with UC. A crucial pathological feature of UC is the impairment of the intestinal mucosal barrier, which underlies aberrant immune responses and inflammation. Intestinal stem cells (ISCs), which differentiate into intestinal epithelial cells, play a central role in maintaining this barrier. Growing studies have proved that regulating the regeneration and differentiation of ISC is a promising approach to treating UC. Despite this progress, there is a dearth of comprehensive articles describing the role of ISCs in UC. This review focuses on the importance of ISCs in maintaining the intestinal mucosal barrier in UC and discusses the latest findings on ISC functions, markers, and their regulatory mechanisms. Key pathways involved in ISC regulation, including the Wnt, Notch, Hedgehog (HH), Hippo/Yap, and autophagy pathways, are explored in detail. Additionally, this review examines recent advances in ISC-targeted therapies for UC, such as natural or synthetic compounds, microbial preparations, traditional Chinese medicine (TCM) extracts and compounds, and transplantation therapy. This review aims to offer novel therapeutic insights and strategies for patients who have long struggled with UC.